Towards resource‐efficient forests: Mixing species changes crown biomass allocation and improves growth efficiency - Torben Hilmers; Lauri Mehtätalo; Kamil Bielak; Gediminas Brazaitis; Miren delRío; Ricardo Ruiz‐Peinado; Gerhard Schmied; Enno Uhl; Hans Pretzsch (Plants, People, Planet)
Societal Impact Statement Forests worldwide face significant challenges due to climate change, impacting their health and productivity. In this study, we examined how European beech and Scots pine influence each other's phenology and growth in mixed forests. Our findings indicate that mixing these complementary tree species can increase resource efficiency within forest ecosystems. By leveraging informed species selection, this research highlights the potential for developing knowledge‐based, resource‐efficient forests. These insights are invaluable for policymakers and forest managers in designing forests that are not only productive but also sustainable and adaptable to evolving environmental conditions. Summary We investigated the effects of interspecific neighbors on crown morphology and growth efficiency in European temperate forests, specifically focusing on European beech (Fagus sylvatica L.) and Scots pine (Pinus sylvestris L.). Our goal was to determine whether the previously reported overyielding in this mixture is primarily due to improved space‐use efficiency and packing density or enhanced resource‐use efficiency. Our methodology involved a detailed analysis of 128 individual felled trees. We assessed the effect of intraspecific and interspecific neighbors on stem volume growth, the allometric relationships of tree crowns and their components, and the allocation of branch and leaf biomass along the trees' vertical structure. Our findings demonstrate that interspecific neighbors significantly influence the allometric relationships of tree crowns, especially altering the vertical biomass distribution in European beech. Additionally, we found that interspecific neighbors can significantly enhance the growth efficiency of European beech but not for Scots pine. This research provides valuable insights for enhancing forest growth models and guiding forest management practices. By understanding the critical role of crown biomass allocation and growth efficiency in mixed‐species stands, policymakers and forest managers can design forests that are both productive and adaptable to changing environmental conditions. This study emphasizes the importance of species interactions in forest dynamics and bridges theoretical concepts with practical applications.